Variations by degrees: Western European paleoenvironmental fluctuations across MIS 13–11. Issue 169 (August 2022) - Hosfield, Robert
Abstract: Marine Isotope Stages (MIS) 13–11 saw a major transformation in the hominin occupation of Europe, with an expansion in the scale and geographical distribution of sites and artifact assemblages. That expansion is explored here in the context of paleoenvironmental variability, focusing on geographical and chronological trends in climatic and habitat conditions at and between key Lower Paleolithic sites in Western Europe. Climatic conditions at British sites are compared across MIS 13–11, and used to test predicted values from the Oscillayers data set. Conditions at hominin and nonhominin sites are compared to explore possible limitations in hominin tolerances during MIS 13–11. Trends in conditions are explored with reference to long-term global patterns, short-term substage events, and seasonal variations. The apparent increase in the scale of hominin activity in north-western Europe during MIS 13 is surprising in light of the relatively harsh conditions of late MIS 13, and is likely to reflect significant physiological and/or behavioral adaptations, a mild south-north temperature gradient in western Europe during MIS 13, and the relatively mild, sustained conditions spanning MIS 15–13. The expanded occupation of north-western Europe during MIS 11 probably reflects the extended mild conditions of MIS 11c, since marked seasonal temperature differences and substantial behavioral changes between hominin sites in MIS 13 and 11 are not clearly evident. Site-specific conditions in south-western Europe during MIS 11 suggest milder winters, warmer summers, and reduced seasonal variability compared to north-western Europe. Some or all of these conditions may have supported larger, core populations, as may the relatively mild conditions associated with south-western European sites during MIS 12. Finally, comparisons between north-western and north-central European sites indicate relatively small differences in seasonal temperatures, suggesting that climate may only be a partial factor behind the smaller-scale occupations of north-central Europe during MIS 13–11. Highlights: Extended MIS 11c mild conditions facilitated hominin expansions in Western Europe. Conditions in southwest Europe suggest the region's role as a core population zone. Bioclim variable gradients suggest hominin dispersals focused in westernmost Europe. Climate partly caused smaller northcentral European occupations in MIS 13 and 11.